Preservative effect of Tetraclinis articulata and Cedrus atlantica wood extractives against fungal decay - Salhi, Noura; Fidah, Abdelwahed; Rahouti, Mohamed; Ismaili, My Rchid; Kabouchi, Bouselham; Famiri, Abderrahim (Instituto de Ecología, A.C., 2020)
Testing environmentaly-friendly plant essential oils for their ability to protect non-durable wood against wood decay fungi is a research topic of current interest. In this study, wood preservative potential of extracts from the wood of the durable species, Tetraclinis articulata and Cedrus atlantica were assessed on non-durable maritime pine sapwood, Pinus pinaster var atlantica, after exposure to three wood decay fungi, according to the EN 113 Standard. Significant differences were observed between treatment effects of these extracts, between fungal decay levels and between oils concentrations. Overall, mean mass losses of treated wood specimens were above 8%. T. articulata root burl extract gave the best protection level for this type of wood against Gleophyllum trabeum and Rhodonia placenta but only at test concentrations above 0.1%v/v. However, efficacy levels of both extracts’ treatments, applied at the tested concentrations, were judged insufficient on the basis of the NF EN 113 standard used.